2009
DOI: 10.1111/j.1365-2648.2009.05177.x
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Breast Cancer Screening Beliefs Questionnaire: development and psychometric testing with Chinese‐Australian women

Abstract: Preliminary data suggest that the Chinese Breast Cancer Screening Beliefs Questionnaire is a valid, reliable and culturally sensitive instrument for the measurement of Chinese-Australian women's beliefs, knowledge and attitudes about breast cancer and breast cancer screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 41 publications
5
61
0
Order By: Relevance
“…The finding that illness attribution beliefs have a significant influence on performance of healthrelated behaviour is consistent with results from Chen (1996), Liang et al (2008) and Kwok et al (2009). The implications of this are important; cancer risk for this group is likely to be heightened over the lifespan because of decision making about physical activity that correlate with TCM illness attributions.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The finding that illness attribution beliefs have a significant influence on performance of healthrelated behaviour is consistent with results from Chen (1996), Liang et al (2008) and Kwok et al (2009). The implications of this are important; cancer risk for this group is likely to be heightened over the lifespan because of decision making about physical activity that correlate with TCM illness attributions.…”
Section: Discussionsupporting
confidence: 83%
“…The difficulty with this goal is alarming to note that the health status of these immigrants tends to decline with time residing in Australia (AIHW, 2002;McCracken et al, 2007). Moreover, data also suggest that Australian women of Chinese ancestry are at a 40% elevated risk of developing cancer compared to age-matched contemporaries remaining in China (Ziegler et al, 1993;Kwok et al, 2009). The explanation for this disparity is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, Champion's HBM scale has been tested for reliability and validity around the globe and translated for Iranian (Hashemian, Shokravi, Lamyian, Hassanpour & Akaberi, 2013;Taymoori & Berry, 2009), Lithuanian (Zelviene & Bogusevicius, 2007), Malaysian (Parsa, Kandiah, Mohd Nasir, Hejar & Nor Afiah, 2008), Arabic (Mikhail & Petro-Nustas, 2001), Korean (Lee, Kim & Song, 2002), Chinese-Australian (Kwok, Fethney & White, 2010), Turkish (Norman & Brain, 2005;Lunt, Bowen & Lee, 2005), African-American (Champion et al, 2008), and Spanish-speaking American women (Medina-Shepherd & Kleier, 2010). Findings of these studies have provided support for the validity and reliability of these HBM-based scales, though poor construct validity was shown in a Peruvian-translated version (Champion et al, 2008) and in a Spanish version (Esteva et al, 2007).…”
Section: History and Development Of The Champion's Health Belief Modementioning
confidence: 99%
“…24,25 A recent survey of Chinese people in UK Midlands region (n = 436) found that exercise was an important factor for Chinese people in preventing heart disease, but they had little knowledge of the correct methods of exercise to achieve health. 26 Data such as these are only just coming to light as elderly migrant populations reach the age when increasing health problems occur.…”
Section: Introductionmentioning
confidence: 99%